Islamic Middle Ages Pottery from Muge (Portugal), Serradinho Archaeological Site—A Long-Lasting Tradition of Pottery Production - Carlos Andrés Camara; Gonçalo Lopes; Nicola Schiavon; José Mirão; Massimo Beltrame (Ceramics, 2025)
During the Islamic period, ceramic workshops were commonly established in settlements throughout the Gharb al-Andalus region (Western Iberia at the time), to produce ceramics for local supply. Along the middle valley of the Tagus river (i.e., nowadays central Portugal), hundreds of Islamic ceramic sherds, either glazed or common wares, were recovered over different archaeological excavations. At the archaeological site of Serradinho, located at Muge (Municipality of Salvaterra de Magos, Santarem District, Portugal), a fortuitous finding was unearthed during agricultural works in which ceramic sherds from the Emiral (8–9th century) to the Almoravid (mid–12th century) period were recorded. The uninterrupted time lapse evidenced by these ceramic artefacts is a one-off opportunity to trace back early Islamic ceramic production and to link it with the long-lasting ceramic tradition documented at Muge by ethnographic studies. In this study, insights into the provenance of raw materials and the pottery-manufacturing processes will be approached by means of different optical and analytical methods, namely Optical Microscopy (OM), X-Ray Diffraction (XRD), X-Ray Fluorescence (XRF), Scanning Electron Microscope, Energy Dispersive X-ray Spectroscopy (SEM-EDS) and granulometric tests on sediments offering some interesting parallels between archaeological and modern ceramic production. Results suggested that most ceramics were locally produced, while others were imported into the settlement during the Islamic Middle Ages. Moreover, data indicate that a locally available raw material which is still used nowadays for the production of traditional ceramics had been employed. This result confirms the exploitation of the same raw material over time, linking Islamic Middle Ages ceramic production to the modern one.